Thermoresponsive polymeric radionuclide delivery system--an injectable brachytherapy - Hruby, Martin; Pouckova, Pavla; Zadinova, Marie; Kucka, Jan; Lebeda, Ondrej (European journal of pharmaceutical sciences, 2011)
Brachytherapy is of increasing popularity in clinical oncology for the local therapy of solid tumors due to high radiation doses delivered to malignant tissue while keeping the whole-body radiation burden low. Pronounced dose-dependent tumor growth reduction was achieved by single dose of injectable intratumoral brachytherapy with iodine-131-labeled thermoresponsive polymer [poly(N-isopropyl acrylamide)] in murine xenograft model (PC3 human prostate adenocarcinoma). The two doses of radionuclide were used, 2 MBq/mouse and 25 MBq/mouse. The higher dose caused gradual tumor volume reduction and 2 of 6 mice from this group were cured. The lower dose caused tumor growth retardation only. In both cases there were no signs of inflammation. The effects of both doses were statistically significant compared to untreated controls. Such injectable system should keep advantages of brachytherapy while making system administration easier and less invasive (injection instead of implantation), patient-tailored (splitting of doses into several depoes) and bioerodable.
Keywords: nosiče léků; akrylové pryskyřice; Drug Carriers; nádorové buněčné linie; dávka záření; Dose-Response Relationship, Radiation; Xenograft Model Antitumor Assays; akrylamidy; Radiopharmaceuticals; radiofarmaka; lidé; Acrylic Resins; mužské pohlaví; vztah dávky záření a odpovědi; nádory prostaty; Mice; Cell Line, Tumor; radioizotopy jodu; Acrylamides; brachyterapie; Polymers; injekce do léze; Mice, Nude; xenogenní modely - testy protinádorové aktivity; Prostatic Neoplasms; zvířata; Humans; Radiation Dosage; Temperature; myši nahé; Brachytherapy; Injections, Intralesional; myši; Solubility; polymery; rozpustnost; Iodine Radioisotopes; teplota; Male; Animals